Communion and agency: research on social workers in China - Zhang, Yangyong (Frontiers in Psychology, 2024)
Communion and agency are two essential dimensions for understanding personality traits. This study comprised 49 in-depth interviews and three focus groups with experienced social workers in China to address the following research questions: (1) What is the orientation of Chinese social workers towards communion and agency? (2) What challenges do they encounter in their daily practice? (3) How do they interpret and utilize agency in coping with these challenges? The findings revealed three main themes: (a) Participants demonstrated a clear preference for communion over agency, reflecting a strong orientation towards social concern; (b) The professional challenges faced by participants varied significantly across career stages, with distinct requirements for agency at each stage; and (c) Participants’ understanding of agency was primarily rooted in professional competence. At different career stages, participants displayed varying levels of professional competence and agency, both of which were essential for addressing social concerns and developing strategies for long-term professional survival. The study suggests that social workers need to balance social concerns with individual development, view social work rationally as an ordinary job, and focus on enhancing both their professional competence and personal agency to achieve their aspirations.